RESULTS OF TROLLING LINE OPERATIONS IN GOA WATERS DURING 1965-68 - Dhawan, Rajinder M; Namboothiri, P V S; Gopinathan, V G (Indian Journal of Fisheries, 2011)
The results of trolling line operations conducted for the first time in Goa waters by the Directorate of Fisheries, Panaji, during the years 1965-68 have been discussed. These operations, in later years, led to starting of a small commercial fishery. The trolling line catches are constituted by Scomberomorus commerson, Chorinemus lysan, Caranx sansun, Sphyraena sp.. Chirocentrus dorab, Rachycentron canadus, Euthytmus affinis and Thynnus mapropterus. The size groups, gonadal condition and food of Scomberomorus commerson and Chorinemus lysan which were the two main species in the fishery have bsen described.